The role of the work environment in achieving career satisfaction among workers: A field study of a sample of workers in some shopping centers in the city of Sulaymaniyah - Husein, Twana Faraidoon (Al-Adab Journal, 2023)
This study focuses on the role of the work environment in achieving career satisfaction among workers. The study questions revolve around the level of career satisfaction among the study sample. What is the position of the study sample members on the factors that affect their level of career satisfaction? Therefore, the factors that affect the level of career satisfaction among the research sample members? The study attempts to answer these questions through the implementation of the field steps and procedures. As for the objectives of the study, it is first to know the level of career satisfaction of the workers, and secondly to know the perceptions of the study sample about the factors affecting the career satisfaction of the workers, Finally, identifying the most influential factors in career satisfaction among the study sample. This study is one of the descriptive studies in which the social survey method was used by the sample method, and a non-probability intended sample was selected from (100) male and female workers in shopping centers in the city of Sulaymaniyah by the social survey method, The researcher also used the five-point Likert scale to measure the extent of career satisfaction and relied on the statistical bag program for social sciences (SPSS) to analyze the items of the scale and discuss the objectives of the study in a scientific way based on descriptive statistics. The results of the study showed that workers have the freedom to express their opinions at work and feel pleasure in implementing them, As for the attitudes of the respondents towards the factors that affect their level of career satisfaction, the results showed that there is a positive perception or perspective among the workers about their careers, The results of the study also showed the existence of an exchange of opinions and suggestions between the workers and their bosses at work, and rewarding the workers by the administrative heads, which is one of the most important factors affecting the position of the studySample with regard to their level of career satisfaction.